Ageing with a lifelong disability : a guide to practice, program, and policy issues for human services professionals - Bigby, Christine (Jessica Kingsley, 2004)
Based on the author's 18 years' research experience and social work practice expertise, this pioneering guide provides up to date specialist knowledge about ageing with a disability in the context of the more mainstream knowledge about ageing processes. Christine Bigby uses the concept of 'successful ageing' as a framework in which to consider the issues and practicalities for older people with a lifelong disability. Bigby presents strategies for the various challenges involved in the physiological, psychological and sociological aspects of ageing and proposes an integrated framework of service development and policy directions for the implementation of these strategies. Particular focus is given to lifestyle planning, encompassing subjects such as daily activity and leisure, housing and support, advocacy, case management and health. Consideration is also given to working with older parental carers of adults with a lifelong disability to support preparation and planning for the transition from parental care.